Observations of Marine Mammals and Other Animals During the Antarctic Expedition of the USSR Academy of Sciences (1957-1958) (Nablyudeniya za Morskimi Mlekopitayushchimi i Drugimi Zhivotnymi v Antarkticheskoi Ekspeditsii Akademii Nauk SSSR (1957-1958 gg.)) - Zenkovich,B. A. (1970)
During 1957/58 The Complex Marine Antarctic Expedition investigated the distribution of cetaceans. About 5000 whales were observed during the 180-day cruise. About 4000 whales were observed during the 105 days in the ice zone of Antarctica. Many whales were encountered beyond the ice boundaries, i.e., in places that are not visited by whaling fleets. Considerable numbers of whales were observed in large polynyas near the ice edge, off the shore ice, which are not investigated by whaling vessels. About 1200 seals were observed on pack ice and on shore ice; most of them were crab eaters. The following species of pinnipeds were noted: crabeating seals, Weddell seals, sea leopards, Ross seals, and, far from pack ice but near icebergs, elephant seals. Near the ice zone large groups of pilot whales and small dophins were observed. However, the small dolphins also occurred among pack ice. Killer whales pursued seals and penguins among ice. In addition, 1138 small whales were observed, namely: 89 rorquals, 1016 killer whales and 33 large beaked dolphins. Outside the ice zone sperm whales were observed of which 830 were identified. The sighted dolphins exceeded 5000. Trans. of Akademiya Nauk SSSR. Ikhtiologicheskaya Komissiya. Trudy Soveshchanii, v12 p23-24 1961, by M. Slessers.